1985
DOI: 10.1080/15287398509530694
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and dietary effects of ethoxyquin hydrochloride

Abstract: Ethoxyquin (EQ, 1,2-dihydro-6-ethoxy-2,2,4-trimethylquinoline) was purified and converted to a crystalline, stable ethoxyquin hydrochloride (EQ-HCl). The readily available (technical grade) oily EQ reacted with concentrated hydrochloric acid (HCl) and precipitated as a crystalline salt (EQ-HCl) in acetone, leaving most of the impurities in solution. The regenerated free base (EQ) from the EQ-HCl was further purified by silicagel column chromatography to remove several minor contaminants, and the pure unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…), and EQ • HCI was prepared by the method described (Kim, 1985). High-performance liquid chromatography (HPLC) grade acetonitrile (MeCN) was purchased from Fisher (Springfield, N.J.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and EQ • HCI was prepared by the method described (Kim, 1985). High-performance liquid chromatography (HPLC) grade acetonitrile (MeCN) was purchased from Fisher (Springfield, N.J.).…”
Section: Methodsmentioning
confidence: 99%
“…Rats were given EQ/corn oil (0.08 g EQ/d/rat) orally for 7 consecutive days and the urine samples were collected at ambient temperature for a 24-h period following 6 d of dosing. Ethoxyquin (free base) was liberated from crystalline EQ • HCI as described (Kim, 1985) and diluted with corn oil, 0.2 g EQ/ml. The urine samples were stored frozen until analyzed.…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…EQ HCI was prepared as described (Kim, 1985) by converting the available dark oily EQ (a gift from Monsanto) into crystalline EQ HCI and was recrystallized several times from methanol-acetonitrile to give a colorless analytical sample (mp 192-193°C). The standard solution was prepared weekly in methanol (10 mg/ml) and immediately diluted with acetonitrile to 0.1 ^g/m\ and kept in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison of EQ and EQ-HCl effects showed that the animals in EQ-HCl group initially lost weight less than the EQ-group, but then gained it faster. 6 It was also shown that EQ-HCl provided protection against toxic doses of pyrrolizidine alkaloids, and its activity was comparable to that of commercial EQ. 4 In our laboratories we have undertaken studies on cytotoxic, genotoxic and antioxidant activities of EQ (purity > 97%) and new potential antioxidants (including different EQ salts) 7,[9][10][11] after reports on harmful health effects observed in animals fed with EQ-containing feeds.…”
Section: Introductionmentioning
confidence: 93%